Ondel-Ondel Culture: People's Perception on the Shifting in Function and Value Degradation - Lambok Hermanto Sihombing (Humaniora, 2023)
Ondel-ondel is one of Jakarta’s most prominent cultures. It is a giant doll made of woods and decorated  with cotton clothes and human-like embellishments. However, there has been a shift in the way people perceive its role. Ondel-Ondel, which was initially used in significant ceremonial contexts, has evolved into a tool for busking or street entertainment, or more commonly known as Ondel-Ondel Ngamen. At the moment, Ondel-Ondel Ngamen has captured big interest of online users on YouTube. There is a variety of comments on YouTube regarding the existence and representation of Ondel-ondel Ngamen. In this study, the author aims to evaluate YouTube comments regarding people's perceptions of the Ondel-Ondel culture. The author applies a qualitative approach by providing the data from the top-three Indonesian news-related YouTube channels; CNN Indonesia, KompasTV, and Metrotvnews. The dataset is taken from any other scholarly articles that support this analysis. In this study, the author utilizes Stuart Hall's encoding-decoding and commodification theories to evaluate how people perceive Ondel-Ondel, which has undergone a shift in function and value degradation. This study's findings indicate that Ondel-Ondel is vulnerable to commodification. It is no longer regarded as a sacred aspect of rituals or noteworthy occasions.